INTERAÇÃO MEDICAMENTOSA ENTRE OS ANTICONCEPCIONAIS ORAIS HORMONAIS COMBINADOS E ANTIBIÓTICOS - Dreon, Bruna; Vassoler, Sabrina; Braghini, Cássia Cristina; Tasca, Fernanda Mahle (Anais de Odontologia / ISSN 2526-9437; v. 3 n. 1 (2018): 2018/1, 2018)
.